Learning Cocoa - Buttfield-Addison, Paris (O'Reilly Media, 2014)
"Learn how to use Cocoa with Objective-C to develop applications on the iOS and OS X platforms. If you don't have experience with Apple's developer tools, no problem! From object-oriented programming to networking with Bluetooth this video course covers all of the essentials you need to build apps for the iPhone, iPad, and Mac."--Resource description page.